2021
DOI: 10.1186/s12876-021-02001-2
|View full text |Cite
|
Sign up to set email alerts
|

An alternative splicing signature in human Crohn’s disease

Abstract: Background Although hundreds of risk loci for Crohn’s disease (CD) have been identified, the underlying pathogenesis of CD remains unclear. Recently, evidence has shown that aberrant gene expression in colon tissues of CD patients is associated with the progression of CD. We reasoned that post-transcriptional regulation, especially alternative splicing (AS), may also play important roles in the pathogenesis of CD. Methods We re-analyzed public mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…With approximately 1.6 million individuals affected and 70,000 new diagnoses each year in the US alone, inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), represents a major health burden [ 1 ]. Nearly 250 single nucleotide polymorphism (SNP)-tagged loci [ 2 , 3 , 4 , 5 ] and chromosomal alterations [ 6 , 7 ], as well as splicing variants [ 8 , 9 ], were linked to an elevated risk of developing IBD. In addition, several studies investigated IBD-induced gene expression changes in the past, including expression quantitative trait loci (eQTL) approaches [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With approximately 1.6 million individuals affected and 70,000 new diagnoses each year in the US alone, inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), represents a major health burden [ 1 ]. Nearly 250 single nucleotide polymorphism (SNP)-tagged loci [ 2 , 3 , 4 , 5 ] and chromosomal alterations [ 6 , 7 ], as well as splicing variants [ 8 , 9 ], were linked to an elevated risk of developing IBD. In addition, several studies investigated IBD-induced gene expression changes in the past, including expression quantitative trait loci (eQTL) approaches [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the results from public or validation RNA-seq dataset all suggested a strong similarity that SE and AFE were the two most common types of AS events in patients with CD. 170 In 2021, a transcriptomic research using RNA-seq was carried out to present the whole mRNA sequencing profiles of 124 biopsies obtained from 34 young donors with UC or CD. In this study, a newly definition of 'spliceopathy' was first supported by Berger et al, 171 and the meaningful results implied that tissue location might be the largest contributor to variability in gene expression and splicing of IBD patients.…”
Section: Transcriptomic Analysis Of As Events In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…To validate the reliability in the GSE66207 dataset, authors also analysed the RNA‐seq data focused on a Chinese cohort and demonstrated 1715 significantly AS events were involved. Interestingly, the results from public or validation RNA‐seq dataset all suggested a strong similarity that SE and AFE were the two most common types of AS events in patients with CD 170 . In 2021, a transcriptomic research using RNA‐seq was carried out to present the whole mRNA sequencing profiles of 124 biopsies obtained from 34 young donors with UC or CD.…”
Section: Transcriptomic Analysis Of As Events In the Pathogenesis Of Ibdmentioning
confidence: 99%
“…STAT3 is alternatively spliced into different functional isoforms, some with altered C-terminal transactivation domains and opposing impacts on signaling. 15 , 16 It is unclear how alcohol exposure impacts STAT3 transcript usage, signaling activity, and ultimately animal behavior.…”
Section: Introductionmentioning
confidence: 99%